Mathematical modeling of drying characteristics for cylindrical Thompson seedless grapes under natural convection. (3rd January 2023) - Komble, Sachin Prabhakar; Kulkarni, Govind; Dhamangaonkar, Pradyumna; Sewatkar, Chandrashekhar
Abstract: The objective of this paper is to develop a universal diffusion model of drying kinetics that can be applied to a variety of shrinkable products such as fruits and vegetables. The main objective is to examine the physical changes that occur during convective air‐drying process of Thompson seedless type cylindrical grapes. These include changes in the physical properties of the product, such as the moisture content, the temperature of the product, and the size of the product. The authors develop a two‐dimensional transient diffusion model and MATLAB that takes into account convection, radiation, and evaporation phenomena under a variety of operating conditions for simulating grape drying and shrinkage. The differential equations are solved for moisture transfer within a cylinder using the finite difference method. A lab‐scale experimental test setup has also been developed and tests are performed. The results obtained from the mathematical model are compared with experimental results and found to be in agreement with a maximum error of 14%. The model is also validated with the results reported in the literature. Meteorological data are used to determine the time‐dependent radiation flux density (I(t)) on a particular day. For each of the investigated conditions, the effective moisture diffusivity ( D eff ) is determined using Fick's diffusion equation. Volume reduction of a product due to drying process was assumed to be equivalent to moisture removal. A coefficient of effective diffusivity was calculated using drying data collected at constant cabin air temperatures between 50 and 70°C. The maximum radius and length of the grape were reduced by 40.33% and 42.40%, respectively, when the size of the grape was considered to be 6.5 mm radius and 25 mm length. The results of the present mathematical model may be useful for accurately predicting the temperature, moisture content, and size change of the product. Practical Application: Drying food to preserve it is an energy‐intensive process. Solar drying is one of the oldest methods used to preserve agricultural produce. Solar thermal energy has tremendous potential for commercial and industrial drying applications with air temperatures as high as 80°C. Solar drying is prevalent in India because farmers have easy access to solar drying systems. Through the installation of such a system, agricultural products can be dried in agricultural regions. This work provides farmers with added value for their particular products. Solar dryers system ensure significant fossil fuel energy savings. Solar dryers must meet rigorous requirements for dependability and continuous operation. This research contributes to the design, optimization, and control of food drying processes. For each drying time, the extent of moisture distribution, product temperature, and product size are determined. For dryers operating under a variety of operating conditions, this aids in system performance forecasting. In addition, the effect of interior cabin temperature variation is investigated, which aids in identifying drying characteristics. Abstract : Graphical abstract with research study flow.